2020
DOI: 10.1055/s-0040-1709687
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Telehealth Supports Care for Neonatal Patients in Strict Isolation

Abstract: Telehealth supports patient care in isolation. • Telehealth reduced health care provider exposures. • Telehealth conserves personal protective equipment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…[12][13][14][15] One recent study used video systems, mobile devices, and digital stethoscopes to reduce both PPE use and exposure of health care workers in the intensive care unit (ICU). 16 These actions are in line with the Centers for Disease Control and Prevention's recommendation that hospitals develop protocols to manage patients with COVID-19 using telehealth or telemedicine methods as part of a comprehensive preparedness checklist. 17 Despite these efforts, much is unknown about the utilization of existing technology capabilities and the details of implementing digital solutions at scale in hospitals during a short time period for disaster responses such as COVID- 19.…”
mentioning
confidence: 73%
“…[12][13][14][15] One recent study used video systems, mobile devices, and digital stethoscopes to reduce both PPE use and exposure of health care workers in the intensive care unit (ICU). 16 These actions are in line with the Centers for Disease Control and Prevention's recommendation that hospitals develop protocols to manage patients with COVID-19 using telehealth or telemedicine methods as part of a comprehensive preparedness checklist. 17 Despite these efforts, much is unknown about the utilization of existing technology capabilities and the details of implementing digital solutions at scale in hospitals during a short time period for disaster responses such as COVID- 19.…”
mentioning
confidence: 73%
“…Characteristics of technologies in the studies. [13-22,25,26,28,30,31,33,34,36-45,47,49-51,54-59,62-64,66-76,78,79,82-89,92,93,96,97, 99-103,105,107-116,118,119] 29,32,35,46,52,53,60,61,65,77,80,90,95,104,106,117] 17 (15.7) Both[20,25,29,34,41,44,45,47,49,51,56,58,61,69,70,73,76,80,81,83,86,[89][90][91][93][94][95]101,[104][105][106][107]114,115,119,120,122,123,[125][126][127][128]131,132,135,136] 46 (58.2) Built for purpose[14-16,18,20,23-26,31,34,37-39,47,50,53,54,57,62-64,67,69-72,74-77,87,90,96,97,100,101,107, 108,111,113,115,117,120,137] [26,29,44,45,52,75,78,81,85,88,89,93-95,103,104,106-109,117-119,121,122,124,126-136,138] 17,20-24,26-33,35,40,42,43,46,49,52,53,55,59-62,65-68,74,76,77,79,81,82,84,8...…”
mentioning
confidence: 99%
“…4,5,21,24,25 Furthermore, with the ongoing COVID-19 pandemic, current circumstances favor feasibility, as telemedicine use has increased substantially in the U.S. and Canadian health care systems. [26][27][28][29][30][31][32] While there are concerns that small, community hospitals may not view telemedicine as practical given the often limited resource availability, we found that hospitals with Level I well newborn nurseries rated teleneonatology more feasible than did hospitals with Level II special care nurseries. As most of our respondents were clinicians (versus administrators), the simplicity of program implementation and utilization may have had a greater impact on feasibility ratings than considerations about program cost.…”
Section: Discussionmentioning
confidence: 57%
“…The survey was conducted during a time when telehealth services expanded significantly across U.S. and Canadian health care systems for inpatient and outpatient care during the COVID-19 pandemic. 27,28,30,31 This greater familiarity with telemedicine may have increased the likelihood of positive provider attitudes toward teleneonatology.…”
Section: Discussionmentioning
confidence: 99%